Half a Pot is Better than No Pot at All: The Role of Accident in Archaeology - Millard, Alan (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The paper illustrates how archaeology has often advanced with discoveriesmade in serendipodus circumstances and how the remains themselves have regularly been the result of ancient accidents. The objects are commonly fragmentary and while they themselves may not be precious the information they and their context may provide can be invaluable. Some of these discoveries have been at odds with accepted wisdom and they caution those who may be inclined to be conclusive about what has not been discovered.